2017
DOI: 10.35188/unu-wider/2017/254-0
|View full text |Cite
|
Sign up to set email alerts
|

Regime type, inequality, and redistributive transfers in developing countries

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…The empirical studies show that democracy based on Polity and income inequality are inversely related, as the degree of democracy increases the level of income inequality decreases (Knutsen, 2011). According to Dodlova and Giolbas (2017) in a democracy because of greater redistribution the income inequality level is low. And a democratic regime that is rich can better reduce income inequality than a democratic regime that is poor (Miguel and Aguilar, 2016).…”
Section: Methodology Theoretical Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The empirical studies show that democracy based on Polity and income inequality are inversely related, as the degree of democracy increases the level of income inequality decreases (Knutsen, 2011). According to Dodlova and Giolbas (2017) in a democracy because of greater redistribution the income inequality level is low. And a democratic regime that is rich can better reduce income inequality than a democratic regime that is poor (Miguel and Aguilar, 2016).…”
Section: Methodology Theoretical Structurementioning
confidence: 99%
“…HI: Political regime type is not negatively and significantly related to income inequality in Pakistan. Dodlova and Giolbas (2017) used annual data for 143 developing countries from 1960 to 2015 to examine the relationship between regime type, inequality, and redistributive transfer. According to the study, there is a higher likelihood of redistribution through various social transfer programs in democracies than in autocracies because pro-poor policies are decided by median voters in democracies, while the elite maximizes their utility in autocracies.…”
Section: The Hypothesis Of the Studymentioning
confidence: 99%
“…Overall, these results provide support to the aims of the United Nations' 2030 Agenda for Sustainable Development (UN-2030-ASD) and the G20 High-Level Principles for Digital Financial Inclusion (G20-HLP-DFI). Dodlova et al (2017) concluded that low-income inequality in democracy is compared to autocracy because democracy increases the probability of redistribution as the elite are elected by the common people, that's why their policies are pro-poor. While in autocracy the situation is unclear because they can increase or decrease the redistribution based on their interest and for the avoidance of social conflicts (Dodlova et al, 2017).…”
Section: Empirical Reviewmentioning
confidence: 99%